The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1055/s-0042-1742526
|View full text |Cite
|
Sign up to set email alerts
|

Novelty in Public Health and Epidemiology Informatics

Abstract: Objectives: To highlight novelty studies and current trends in Public Health and Epidemiology Informatics (PHEI). Methods: Similar to last year’s edition, a PubMed search of 2021 scientific publications on PHEI has been conducted. The resulting references were reviewed by the two section editors. Then, 11 candidate best papers were selected from the initial 782 references. These papers were then peer-reviewed by selected external reviewers. They included at least two senior researchers, to allow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…ML models have proven to be helpful in the medical and health sciences, particularly in the areas of diagnosis and outcome prediction (27). Previous research has suggested that the application of ML models in the healthcare industry, although still in the early stages, is primarily focused on the early diagnosis of chronic diseases, predicting future disease incidence, conducting epidemiological studies, and facilitating evidence-based decision-making (27)(28)(29)(30)(31)(32). There is also evidence supporting the use of AI and ML models to predict AMR among bacterial species based on whole genome sequencing (12,13,(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…ML models have proven to be helpful in the medical and health sciences, particularly in the areas of diagnosis and outcome prediction (27). Previous research has suggested that the application of ML models in the healthcare industry, although still in the early stages, is primarily focused on the early diagnosis of chronic diseases, predicting future disease incidence, conducting epidemiological studies, and facilitating evidence-based decision-making (27)(28)(29)(30)(31)(32). There is also evidence supporting the use of AI and ML models to predict AMR among bacterial species based on whole genome sequencing (12,13,(34)(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the last edition of the IMIA Yearbook for the PHEI section [3], a comprehensive literature search was performed by the section editors using the PubMed/ MEDLINE database from the National Center for Biotechnology Information (NCBI). A large set of MeSH descriptors were used to retrieve relevant studies ranging from January 1, 2022 to December 31, 2022.…”
Section: Methodsmentioning
confidence: 99%
“…Among the two best papers presented by Georgeta Bordea, Gayo Diallo and Cécilia Samieri, the editors of the Public Health and Epidemiology Informatics (PHEI) section [32], the paper from Valentin et al [33] was linked to the One Health topic, more precisely to the annotation of news articles containing epidemiological information on animal diseases. Following on from the theme of the previous yearbook, He et al have carried out a review of recent works which take account of the social determinants of health to promote equity in health [34].…”
Section: One Health and Medical Informaticsmentioning
confidence: 99%